2018
DOI: 10.1002/hbm.23940
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of subjective CS/UCS association in appetitive conditioning

Abstract: Explicit knowledge of conditioned stimulus (CS)/unconditioned stimulus (UCS) associations is proposed as important factor in classical conditioning. However, while previous studies have focused on its roles in fear conditioning, it has been neglected in the context of appetitive conditioning. The present functional magnetic resonance study aimed to investigate neural activation and functional connectivity linked to subjective CS/UCS association in appetitive conditioning. In total, 85 subjects participated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 67 publications
(111 reference statements)
1
25
1
Order By: Relevance
“…Regarding the first, it is difficult to determine a US whose rewarding properties or subjective pleasantness is inter‐individually equivalent. So far, a variety of both primary and secondary stimuli have been used for appetitive reinforcement, for example, food (Andreatta & Pauli, ; Blechert, Testa, Georgii, Klimesch, & Wilhelm, ; van den Akker et al, ; Wardle, Lopez‐Gamundi, & Flagel, ), drink (Ebrahimi et al, ; O'Doherty, Buchanan, Seymour, & Dolan, ; O'Doherty, Dayan, Friston, Critchley, & Dolan, ; Pauli et al, ; Prévost, McNamee, Jessup, Bossaerts, & O’Doherty, ), odor (Gottfried, O'Doherty, & Dolan, ; Hermann, Ziegler, Birbaumer, & Flor, ; Stussi, Delplanque, Corai, Pourtois, & Sander, ), attractive faces (Bray & O'Doherty, ), erotic images (Klucken et al, , , ; Klucken, Wehrum‐Osinsky, Schweckendiek, Kruse, & Stark, ), and money (Austin & Duka, ; Delgado, Gillis, & Phelps, ; Ebrahimi et al, ; Tapia León, Kruse, Stalder, Stark, & Klucken, ). Although there exists a certain overlap, primary and secondary rewards are processed in distinct neural systems (Sescousse, Caldú, Segura, & Dreher, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the first, it is difficult to determine a US whose rewarding properties or subjective pleasantness is inter‐individually equivalent. So far, a variety of both primary and secondary stimuli have been used for appetitive reinforcement, for example, food (Andreatta & Pauli, ; Blechert, Testa, Georgii, Klimesch, & Wilhelm, ; van den Akker et al, ; Wardle, Lopez‐Gamundi, & Flagel, ), drink (Ebrahimi et al, ; O'Doherty, Buchanan, Seymour, & Dolan, ; O'Doherty, Dayan, Friston, Critchley, & Dolan, ; Pauli et al, ; Prévost, McNamee, Jessup, Bossaerts, & O’Doherty, ), odor (Gottfried, O'Doherty, & Dolan, ; Hermann, Ziegler, Birbaumer, & Flor, ; Stussi, Delplanque, Corai, Pourtois, & Sander, ), attractive faces (Bray & O'Doherty, ), erotic images (Klucken et al, , , ; Klucken, Wehrum‐Osinsky, Schweckendiek, Kruse, & Stark, ), and money (Austin & Duka, ; Delgado, Gillis, & Phelps, ; Ebrahimi et al, ; Tapia León, Kruse, Stalder, Stark, & Klucken, ). Although there exists a certain overlap, primary and secondary rewards are processed in distinct neural systems (Sescousse, Caldú, Segura, & Dreher, ).…”
Section: Introductionmentioning
confidence: 99%
“…Psychophysiological measures similarly often present inconsistent results. Electrodermal activity, which is a common learning index used in aversive conditioning paradigms (Lonsdorf et al, ; Ney et al, ), has shown both an enhanced skin conductance response (SCR; Andreatta & Pauli, ; Ebrahimi et al, ; Klucken et al, , , ; Tapia León et al, ), as well as no differential response (Klucken et al, ; Stussi et al, ; van den Akker et al, ) to the reward‐associated stimulus and appears to be dependent on task context (van den Akker et al, ). Heart period response (HPR) has seldom been examined in an appetitive context and has not yielded a conclusive differential effect (Hermann, Ziegler, Birbaumer, & Flor, ; Wardle et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In line with our findings, Chase et al () showed in their meta‐analysis that involvement of the amygdala is specific to acquisition of classical conditioning in contrast to tasks focusing instrumental learning. The NAcc has mainly been associated with acquiring the subjective CS/UCS‐association and contingency awareness (Klucken, Schweckendiek et al, ; Tapia León et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…After few pairings, presenting the CS+ elicits conditioned responses as compared to the CS−. These include higher subjective ratings of valence and arousal, increased skin conductance responses (SCRs), and increased BOLD responses in brain areas associated with conditioning and reward processing (Andreatta & Pauli, ; Tapia León, Kruse, Stalder, Stark, & Klucken, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation